Requirements for a Metadata Scheme to Enable FAIR Energy Research Software - Ferenz, Stephan; Werth, Oliver; Nieße, Astrid (Electronic Communications of the EASST, 2025)
Energy Research Software (ERS) plays a significant role in energy research, by aiding with visualization, simulation, and analysis. To enhance its efficiency, metadata are crucial for better findability, accessibility, interoperability, and reusability (FAIR) of research software. The current approaches to metadata for ERS have multiple limitations, e.g., they are not based on a systematic approach to include the diverse requirements of energy researchers. To address this issue, a qualitative study was conducted to gather specific requirements for metadata for ERS. The findings show the need for additional metadata elements for research software, e.g., on the community or the support options. Also, domain-specific metadata are required, e.g., on time and geographical scope of an ERS. Subsequently, a domain model was developed based on the requirements that lays the foundation for creating a metadata scheme for ERS.